Children with Epilepsy and Anxiety: Subcortical and Cortical Differences - Jones, Jana E. (Epilepsia, 2015)
OBJECTIVE: Using a hypothesis driven approach, subcortical and cortical regions implicated in anxiety disorders in the general population were examined in children with recent-onset epilepsy with versus without anxiety compared to controls. This study reports frequency of anxiety disorders while examining familial, clinical and demographic variables associated with anxiety in children with epilepsy. METHOD: Participants included 88 children with epilepsy aged 8–18 years; 25 with a current anxiety disorder and 63 children with epilepsy no current anxiety disorder. 49 controls without anxiety disorders were included. T1 volumetric MRI scans were collected; subcortical volumes and cortical thickness were computed using the FreeSurfer image analysis suite. Analyses focused on adjusted measures of subcortical volumes and cortical thickness. RESULTS: Relative to controls, larger left amygdala volumes were found in the Epilepsy Anxiety group compared to the Epilepsy No Anxiety group (p = 0.027). In the hippocampus there were no significant differences between groups. Examination of cortical thickness demonstrated that the Epilepsy Anxiety group showed thinning in left medial orbitofrontal (p=0.001), right lateral orbitofrontal (p=0.017), and right frontal pole (p=0.009). There were no differences between groups in age, sex, IQ, age of onset, medications, or duration of epilepsy. There were more family members with a history of anxiety disorders in the Epilepsy Anxiety group compared to the Epilepsy No Anxiety group (p=0.005). SIGNIFICANCE: Anxiety is a common psychiatric comorbidity in children with recent-onset epilepsy with volumetric enlargement of the amygdala and thinner cortex in orbital and other regions of prefrontal cortex, suggesting structural abnormalities in brain regions that are part of the dysfunctional networks reported in individuals with anxiety disorders in the general population. These findings are evident early in the course of epilepsy, are not related to chronicity of seizures, and may be linked to a family history of anxiety and depressive disorders.